Correctional Facilities (IntechOpen, 2025)
How do correctional facilities balance punitive and rehabilitative approaches? What do current policies that shape today’s correctional system support, and what changes are these facilities incorporating into their practices to meet the modern social complexities? Correctional Facilities - Policies, Practices, and Challenges explores those critical questions. This comprehensive volume covers the ever-changing landscape of correctional institutions across the world, providing an extended analysis of the range of policies that shape their functioning, practices carried out inside, and a host of challenges such as overcrowding, inmate rights, mental health, and staff well-being. The book critically analyzes the successes and shortcomings of the present correctional models through empirical research and case studies. This book will become a vital addition to the library of any criminal justice professional, policymaker, scholar, or student interested in learning from operational realities facing correctional facilities nationwide. It consequently constitutes a seminal source for a deepened understanding of the complex functions that such facilities serve in society and initiates important discussions of what the future of incarceration, rehabilitation, and reform might look like.